Eul-Soo Pang, In pursuit of honor and power, Noblemen of the southern in Nineteenth-Century Brazil (Tuscalooza and London Press: University of Alabama Press, 1988). - Marcus J.M. de Carvalho (Clio: Revista de Pesquisa Histórica)
Eul-Soo Pang, In pursuit of honor and power, Noblemen of the southern in Nineteenth-Century Brazil (Tuscalooza and London Press: University of Alabama Press, 1988).